KREATIVITAS GURU PAI DALAM MENGEMBANGKAN MEDIA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Atina Rahmatia; Qiso, Ahmad; Muhammad Wahyudi (Najah Bestari, 2025)
Teachers' creativity in developing learning media plays a crucial role in providing engaging, relevant, and effective learning experiences that benefit the learning process. However, there is still a lack of knowledge among Islamic Education (PAI) teachers regarding learning media, such as their limited mastery of software. The purpose of this research is to investigate and describe how teachers’ creativity is applied in developing learning media at SDN 7 Pemulutan Barat, as well as to identify and describe the supporting and inhibiting factors in the development of learning media at SDN 7 Pemulutan Barat. This study employs a qualitative descriptive approach (field research). The research method uses a qualitative approach with the theme